Nomenclatural and taxonomic survey of the South American clade of Lobelia section Rhynchopetalum (Campanulaceae) - Rollim, Isis De Mello; Peres Coelho, Guilherme; Teresinha Sfoggia Miotto, Silvia; Ricardo Vieira Iganci, João; Trovó Lopes De Oliveira, Marcelo (Phytotaxa, 2022)
Lobelia is the largest genus within the subfamily Lobelioideae of Campanulaceae, comprising 415 species and ranging from small to exuberant woody herbs. In an attempt to clarify the systematics of Lobelia, a nomenclatural and taxonomic survey of its section Rhynchopetalum for South America is here presented. This group is monophyletic and consists of ten species, whose important distinguishing characters are the robust habit, often woody and pachycaulous, terminal racemes of large sub-bilabiate flowers, with only the ventral anthers bearded, and capsules producing numerous lenticular, commonly winged, seeds with a striate-reticulate testa. Along with a synopsis of the group, an identification key, and a distribution map, we also propose seven lectotypifications (for L. fistulosa, L. glazioviana, L. hassleri, L. hilaireana, L. langeana, L. organensis, and L. uranocoma) and four new synonymizations (for Haynadia organensis var. insignis, L. imperialis, L. imperialis var. kanitzii, and L. stellfeldii).